Profiles in understanding the density of rational numbers among primary and secondary school students Perfiles en la comprensión de la densidad de los números racionales en estudiantes de educación primaria y secundaria - González-Forte Juan Manuel; Fernández Ceneida; Van Hoof Jo; Van Dooren Wim (SOC ESPANOLA INVESTIGACION & EDUCACION MATEMATICA-SEIM, 2022)
The present cross-sectional study investigated 953 fifth to tenth grade students' understanding of the dense structure of rational numbers. After an inductive analysis, coding the answers based on three types of items on density, a TwoStep Cluster Analysis revealed different intermediate profiles in the understanding of density along grades. The analysis highlighted qualitatively different ways of thinking: i) the idea of consecutiveness, ii) the idea of a finite number of numbers, and iii) the idea that between fractions, there are only fractions, and between decimals, there are only decimals. Furthermore, our profiles showed differences regarding rational number representation since students first recognised the dense nature of decimal numbers and then of fractions. Learners, however, were still found to have a natural number-based idea of the rational number structure by the end of secondary school, especially when they had to write a number between two pseudo-consecutive rational numbers.
En este estudio transversal sobre la densidad de los números racionales participaron 953 es-tudiantes desde 5º curso de educación primaria hasta 4º curso de educación secundaria. Tras un análisis inductivo, codificando las respuestas a tres tipos de ítems, se llevó a cabo un análisis clúster, que reveló diferentes perfiles intermedios en la comprensión de la densidad. Se identificaron formas de pensar dife-rentes: i) la idea de consecutivo, ii) la idea de número finito de números, y iii) la idea de que entre fracciones solo hay fracciones y entre decimales solo hay decimales. Además, se obtuvieron diferencias con respecto a la representación de los números racionales: los estudiantes primero reconocieron la densidad en núme-ros decimales y posteriormente, en fracciones. Se destaca que los estudiantes al final de la educación se-cundaria todavía tenían una idea basada en el conocimiento del número natural, especialmente cuando tenían que escribir un número entre dos números racionales pseudo-consecutivos.